The Basic Factors Driving The Intention To Pay Zakat - Mariyanti, Tatik; Zaenul Basri, Yuswar; Jazuli, Jozi (Pandawan, 2022)
The role of zakat is significant not only as a means of worship but also zakat has a powerful social and economic aspect. Many previous studies have found that zakat that can be appropriately managed will solve social problems such as the gap between the rich and the poor, social jealousy, etc. In addition, zakat in economic terms was also found to reduce poverty rates, encourage economic growth and increase welfare. In this study, the factors considered are knowledge, attitudes, moral norms, and descriptive norms. Knowledge is related to the ability that is generally owned by someone pertaining to tithe activities. The research method that will be used is using the structural equation model method. With this method, it is hoped that the impact, both direct and indirect, will be seen in detail. This study indicates that the knowledge of a muzzaki and the moral norms he adheres to influence the person's intention to pay zakat significantly. Furthermore, in this study, it is also known that moral norms have a stronger impact between the two, namely knowledge and moral norms. In addition, this study also found that descriptive norms and attitudes did not significantly affect the intention to pay zakat on muzakki. The results of this study can be used in building tithe intentions, especially for zakat institutions, in terms of creating and building messages and appeals that are more appropriate for muzzaki.